P008 An audit of time to treatment for bacterial STIs, and time to provision of HIV diagnosis, in a large urban sexual health clinic. (30th June 2016) - Snow, Anthony; Fortune, Ria; Chen, Marcus; Fairley, Christopher; Lee, David
Abstract : Background: The time from testing to treatment of STIs, and the provision of a new HIV diagnosis*, is a marker of quality of care. The follow-up of positive results is undertaken by nurses according to predetermined protocols. In April 2015 gonococcal NAAT superseded the relatively insensitive gonococcal culture test. Aims: The aims were to determine the time to treatment for HIV*, syphilis, gonorrhoea and chlamydia; and if the introduction of gonorrhoea NAAT affected the time to treatment. Methods: This observational study compared the median time (days) to treatment for HIV* and STIs in two time periods (P1: April-June 2014 and P2: April-June 2015). For gonorrhoea, the median time from testing to result complete and median follow-up time to treatment were also compared. The Mann-Whitney U Test for two independent samples was used to compare medians. Results: The median time to treatment for all STIs, including HIV*, was 8 days or less in P1 and P2 (all p ≥ 0.08). The time to result complete for gonorrhoea was significantly less in P2 (n = 189, median = 3) compared to P1 (n = 50, median = 5) (p = 0.000). However, the median follow-up time to treatment was not significantly different between P1 (median = 3) and P2 (median = 4) (p = 0.4). Discussion/Conclusion: The median time to treatment for HIV*, syphilis, gonorrhoea and chlamydia was not significantly different between P1 and P2. Despite gonorrhoea NAAT results being available significantly earlier, the overall time to treatment was not different. This likely relates to the nearly fourfold increase in the detection of gonorrhoea and the additional burden of work for follow-up nurses.